Physical and mental health impairments experienced by operating surgeons and camera-holder assistants during laparoscopic surgery: a cross-sectional survey - Liu, Junjie; Qiao, Xi; Xiao, Yi; Deng, Zhuofan; Cui, Ji; Wu, Mingdong; Zhang, Haolong; Ran, Kun; Luo, Hailong; Tang, Bo (Frontiers in Public Health, 2023)
Introduction Surgeons may experience physical and mental health problems because of their jobs, which may lead to chronic muscle damage, burnout, or even withdrawal.However, these are often ignored in camera-holder assistants during laparoscopic surgery. We aimed to analyze the differences between operating surgeons and cameraholder assistants.From January 1, 2022, to December 31, 2022, a cross-sectional survey was conducted to evaluate the muscle pain, fatigue, verbal scolding, and task load for operating surgeons and camera-holder assistants. The Nordic Musculoskeletal Questionnaire, the Space Administration Task Load Index, and the Surgical Task Load Index (SURG-TLX) were combined in the questionnaire.Results: 2184 operations were performed by a total of 94 operating surgeons and 220 camera assistants. 81% of operating surgeons and 78% of camera-holder assistants reported muscle pain/discomfort during the procedure. The most affected anatomic region was the shoulders for operating surgeons, and the lower back for camera-holder assistants. Intraoperative fatigue was reported by 41.7% of operating surgeons and 51.7% of camera-holder assistants. 55.2% of camera-holder assistants reported verbal scolding from the operating surgeons, primarily attributed to lapses in laparoscope movement coordination. The SURG-TLX results showed that the distributions of mental, physical, and situational stress for operating surgeons and camera-holder assistants were comparable.Conclusions: Like operating surgeons, camera-holder assistants also face similar physical and mental health impairments while performing laparoscopic surgery.Improvements to the working conditions of the camera-holder assistant should not be overlooked.